Empowering Post-Disaster Psychosocial Support in a Total Defense Perspective - Firsty Yukaputri; Almuchalif Suryo; Priyanto Priyanto (International journal of technology and education research, 2026)
Disasters inflict multidimensional crises that severely disrupt psychosocial well-being, community cohesion, and regional stability. While physical infrastructure reconstruction often takes precedence in emergency management, restoring the psychological fortitude of affected populations is equally vital for long-term national security. This study evaluates the strategic importance of empowering post-disaster psychosocial support, specifically trauma healing interventions, through the lens of a Total Defense perspective. Employing a qualitative research methodology alongside a systematic literature review, this paper examines how local community empowerment and mental health recovery intersect with non-military defense capabilities. The findings indicate that prolonged psychological trauma, if left unaddressed, severely compromises adaptive capacity, collective morale, and social trust, thereby weakening the foundational pillars of societal resilience. Conversely, structured trauma healing mechanisms, such as psychological first aid, group counseling, religious coping approaches, and community-led psychosocial activities, that significantly restore collective emotional stability and rebuild shattered social networks. From a Total Defense standpoint, an empowered, cohesive, and psychologically resilient population serves as the essential civilian core of the nation’s non-military defense component. Therefore, psychosocial rehabilitation should not merely be viewed as a temporary humanitarian response, but as a structural mandate within territorial defense empowerment to mitigate non-traditional security threats. However, several critical challenges persist in post-disaster territories, including fragmented institutional coordination, a severe shortage of trained personnel, and resource constraints. This study concludes that integrating psychosocial support into long-term defense planning and disaster management frameworks is imperative. Strengthening psychological resilience at the grassroots level directly solidifies community-based defense capacity, ensuring sustainable societal stability and national preparedness in disaster-prone areas.